Not Your Usual Bioisostere: Solid State Study of 3D Interactions in Cubanes. Issue 28 (14th March 2019) - Flanagan, Keith J.; Bernhard, Stefan S. R.; Plunkett, Shane; Senge, Mathias O.
Abstract: Previous studies by Desiraju and co‐workers have implicated the acidic hydrogen atoms of cubane as a support network for hydrogen bonding groups. Herein we report a detailed structural analysis of all currently available 1, 4‐disubstituted cubane structures with an emphasis on how the cubane scaffold interacts in its solid‐state environment. In this regard, the interactions between the cubane hydrogen atoms and acids, ester, halogens, ethynyl, nitrogenous groups, and other cubane scaffolds were cataloged. The goal of this study was to investigate the potential of cubane as a substitute for phenyl. This could be achieved by analyzing all contacts that are directed by the cubane hydrogen atoms in the X‐ray crystal structures. As a result, we have established several new cubane interaction profiles, such as the catemer formation seen in esters, the preferences of halogen–hydrogen contacts over direct halogen bonding, and the stabilizing effects caused by the cubane hydrogen atoms interacting with ethynyl groups. These interaction profiles can then be used as a guide for designing cubane bioisosteres of known materials and drugs containing phenyl moieties. Abstract : How the dice rolls : Cubanes have been successfully used as bioisosteres for benzene rings, but most of these studies rely on the fact that the 1, 4‐axis of both these compounds are of similar length. However, with its 3D geometry, cubane has a significant difference in the types of interactions that occur in comparison to benzene. Here, we highlight the differences by an in‐depth study on cubane–hydrogen interaction profiles with multiple functional groups.